Phytochemical and Pharmacognostical Investigation on Ammania baccifera Linn Stem and Leaf - Jani, Switu (International Journal of Pharmaceutical & Biological Archive, 2012)
Phytochemical and Pharmacognostical Investigation on Ammania baccifera Linn Stem and Leaf